The Great Lakes - Katz Cooper, Sharon (New York : Benchmark Books, 1999)
Describes the formation of the Great Lakes, the varied lifeforms that are part of this ecosystem, the interactions among the plants and animals that live there, and threats to this environment.
Includes bibliographical references and index.
Keywords: Ecology -- Great Lakes (North America) -- Juvenile literature; Ecology -- Great Lakes (North America); Freshwater ecology